Amygdala deactivation as a neural correlate of pain processing in patients with borderline personality disorder and co-occurrent posttraumatic stress disorder - Kraus, Anja; Esposito, Fabrizio; Seifritz, Erich; Di Salle, Francesco; Ruf, Matthias; Valerius, Gabriele; Ludäscher, Petra; Bohus, Martin; Schmahl, Christian (Biological psychiatry, 2009)
Background - Previous studies have revealed altered affective pain processing in patients with borderline personality disorder (BPD) as well as in patients with posttraumatic stress disorder (PTSD). Reduced levels of activation in the amygdala might be related to antinociceptive mechanisms pertinent to both disorders. This study aimed at clarifying whether central antinoceptive mechanisms discriminate BPD patients with and without co-occurrent PTSD. - Methods - We investigated 29 medication-free female outpatients with BPD, 12 with and 17 without co-occurrent PTSD. Psychophysical characteristics were assessed, and functional magnetic resonance imaging was performed during heat stimulation with stimuli adjusted for equal subjective painfulness. - Results - No difference in pain sensitivity was found between both groups of patients. Amygdala deactivation, however, was more pronounced in BPD patients with co-occurrent PTSD compared with those without PTSD. Amygdala deactivation was independent of BPD symptom severity and dissociation. - Conclusions - Amygdala deactivation seems to differentiate patients who meet criteria for both BPD and PTSD from BPD patients without co-occurrent PTSD. On the basis of these preliminary findings it might be speculated that reduced pain sensitivity or at least the emotional component of it is associated with amygdala deactivation in patients with both disorders, whereas BPD patients without PTSD use different yet unknown antinociceptive mechanisms.